The differences of work stress on teachers based on demographic factors - Yunita Khairani; Marjohan Marjohan; Riska Ahmad (Universitas Negeri Padang, 2021)
Work stress is an emotional state that arises because of a mismatch between the workload and the individual's ability to cope with the work stress he or she faces. The stress experienced by teachers in carrying out their duties at school cannot be separated from the demands of professional duties as professional teachers, the work done must be maximal. This can be seen from the phenomenon found in the field against equivalent high school teachers in Kerinci Regency, based on an analysis of existing documents in 2019-2020, namely, there are still teachers who are late for attendance even though they have used electronic absences, and are late for teaching in class. There are also teachers who only give assignments to students in class, but the teacher remains in the office. Some teaching teachers do not use creative learning media to attract students' interest, but teach with lecture methods that seem monotonous, boring and not conducive. This study uses a quantitative approach with descriptive and comparative methods with a sample of 212 teachers selected usingthe Two Stage Cluster Random Sampling technique and data collection tools using a questionnaire with a Likert scale model about work stress on teachers. The results of the study revealed that teacher work stress was in the moderate category, and there is a significant difference in work stress by gender with a significance of 0.002, a significance of age 0.049, a significance of length of work 0.00, and a significance of employment status 0.038 with a negligible < 0.05. This research has implications as input for Counselors who operationally consult with school principals and jointly discuss services/activities that can help teachers to minimize stress levels experienced by teachers.